Klasterisasi Hasil Belajar Matematika dengan Algoritma K-Means Clustering - Febrinita, Filda; Puspitasari, Wahyu; Zaman, Wahid (Universitas Nusantara PGRI Kediri, 2023)
Mathematics has an important role in the computer field and provides a theoretical foundation for people working in the computer field. The facts show that in the Informatics Engineering study program, Unisba Blitar, the selection of specializations is carried out without considering the grades of courses that teach basic mathematical skills. In fact, mathematical ability is needed by a computer expert. For this reason, research was conducted that aimed to cluster student mathematics learning outcomes. Clustering was carried out on 51 students in semester 4, through the application of the K-means clustering algorithm. The attributes used are school origin data, majors currently in high school, and student learning outcomes in informatics logic, statistics, computational mathematics, and advanced computational mathematics courses. The results show that through clustering with the K-Means Clustering algorithm, 5 clusters are obtained, starting from the highest average score, namely cluster 2 with a value of 86.81 and the lowest average value is cluster 5 with a value of 76.50. In cluster 2, it is dominated by students from SMK graduates majoring in TKJ. Meanwhile, cluster 5 was dominated by students from high school graduates majoring in natural sciences. In addition, there are findings indicating that vocational high school graduates do not always have lower mathematical abilities than high school graduates, because intrinsic motivation also influences the level of learning outcomes.